Effect of Oral Administration of Valerian Extract at Different Doses on Pharmacokinetic Parameters of Carbamazepine in Rabbits - Issam Mohammed Abushammala (College of Pharmacy University of Baghdad, 2022)
Carbamazepine (CBZ) is a narrow therapeutic index drug used in the treatment of trigeminal neuralgia and psychiatric disorders. Valerian (VAL) is a popular herbal product which should be prescribed to treat insomnia and anxiety. The study was designed to investigate the presence of significant pharmacokinetic (PK) interaction between Valerian (VAL) at different concentrations on Carbamazepine (CBZ) pharmacokinetic parameters in healthy male rabbits. In an in vivo, parallel-randomized controlled trial, the rabbits in three groups "first (control), second and third" were given oral doses of CBZ (50 mg/kg), for "second and third" groups (as test groups) rabbits were given (20 and 40 mg/kg/day) of the VAL respectively, as  suspension in normal saline for eight consecutive days. On the eighth day, CBZ was co-administered an hour after adding the last dose of VAL suspension. Venous blood samples (1.0-1.5 mL) were obtained from rabbits' ears' marginal vein at predetermined different periods. The plasma of this blood separation was done using centrifugation and stored at -80°C, prior to analysis by using CBZ chemiluminescent enzyme immunoassay detection kit. Different PK parameters such as Cmax, tmax, t½,  ke, AUC0-24 and AUC0-∞ were determined for the three groups, applying Statistical testing (ANOVA). The results showed statistical insignificant differences for all PK parameters among the three groups with (p˃0.05). The findings showed that VAL at both concentrations is not likely to interfere with PK parameters related to CBZ, Further confirmation in humans shoud be done before these findings are applied to patient care.